MENGATASI PERMASALAHAN SOSIAL EMOSIONAL ANAK USIA DINI MELALUI PENDEKATAN PEMBELAJARAN KOOPERATIF BERBANTUAN SMART BOX - Nur Khalisah; Ade Veni Yunianti Simanjuntak; Melinda Butar-Butar; Karina Andhini; Hendra Sofyan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the application of cooperative learning assisted by smart box media in addressing social emotional problems in early childhood. This study uses a descriptive qualitative approach with 12 children aged 5-6 years in one PAUD class as subjects. Data collection techniques were carried out through observations of children's social emotional behavior during cooperative learning activities assisted by smart box. The results of the study indicate positive developments in children's social emotional aspects, such as increased ability to cooperate, share, wait for turns, communicate, and control emotions. The use of smart box media can increase children's involvement and interaction in learning activities so that the learning atmosphere becomes more enjoyable and meaningful. Thus, cooperative learning assisted by smart box can be used as an alternative learning strategy in supporting the social emotional development of early childhood.